High school English-as-a-foreign-language teachers’ emotional labor and job satisfaction: A latent profile analytical approach - Zhu, Shenhai; Zhou, Maojie (Frontiers in Psychology, 2022)
Teachers’ emotional labor strategies have been conceptualized as surface acting, deep acting, and expression of naturally felt emotion. Research has shown that the correlation between each emotional labor strategy and job satisfaction of teachers is significant. These findings primarily used a variable-centered approach to explore the correlation between emotional labor strategies and outcome variables. A fundamental but unresolved question is whether teachers employ multiple emotional labor strategies in the workplace. Therefore, this study used the latent profile analysis (LPA) to explore the profiles of EFL teachers' emotional labor and the relationship between these profiles and job satisfaction based on a questionnaire survey of 388 high school EFL teachers in China. Three emotional labor profiles were finally identified, and results indicated that teachers with different latent profiles are reported significantly different levels of job satisfaction. These findings provide a person-centered methodological data support for exploring the relationship between emotional labor and job satisfaction of EFL teachers.